연령별 체질량지수 3백분위수 미만을 희망하는 여고생의 식습관과 심리적 상태 - 박혜영; 이홍미; Park, Hyeyoung; Lee, Hongmie (Korean journal of community nutrition, 2013)
The widespread pursuit for the thin physique may have detrimental impact on the wellbeing of the young generation, especially females. This study aimed to determine the effect of wanting very low body weight on dietary habits and psychological factors of female adolescents. Participants were 619 girls from 5 high schools in Kyeonggi, Korea. Information on dietary behaviors, psychological factors as well as current heights and weights and the desired weight for current height were obtained by questionnaire. Of total subjects, 38.1%, 35.5%, and 26.5% desired weights corresponding to normal (10~85 percentile), low (3~10 percentile) and very low BMI (< 3 percentile), respectively. The subjects who wanted to be very low weight had the average BMI of 18.57 kg/m2, which was significantly lower than $21.21kg/m^2$ of those who wanted to be normal weight (p < 0.001). The subjects who desired very low weight had significantly higher scores for depression symptoms (p < 0.05), while there were no differences in obsession to lose weight and obesity stress. Moreover, more subjects in this group had undesirable dietary habits such as eating fast foods more than weekly (p < 0.05). These findings suggest that the desire for extreme thinness may lead female adolescents to have not only unreasonably similar obesity stress and obsession to lose weight but also higher depression symptoms, along with undesirable dietary habits. The findings suggest the potential harm from excessive weight concerns of female adolescents; thus efforts to teach this group about healthy weights are urgently needed.